2019
DOI: 10.1097/pai.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Deficiency in Endometrial Cancer: Immunohistochemistry Staining and Clinical Implications

Abstract: Introduction: DNA mismatch repair (MMR) deficiency is associated with increased risk of developing several types of cancer and is the most common cause of hereditary endometrial cancer. Identification of the microsatellite instability (MSI) phenotype in endometrial carcinoma is important given that such tumors are frequent. Objective: The objective of this study was to assess the utility of immunohistochemistry (IHC), a simple and fast technique, in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…In this study, we identi ed MMR-D TCs and investigated their mutation pro les, clinicopathological features, and prognostic signi cance. Previous studies have shown that the MMR-D phenotype occurs not only in hereditary non-polyposis CRC but also in endometrial cancer and breast cancer [21][22][23]. Mutations in MMR genes have been reported in approximately 14% of ATC cases [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identi ed MMR-D TCs and investigated their mutation pro les, clinicopathological features, and prognostic signi cance. Previous studies have shown that the MMR-D phenotype occurs not only in hereditary non-polyposis CRC but also in endometrial cancer and breast cancer [21][22][23]. Mutations in MMR genes have been reported in approximately 14% of ATC cases [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that 1 of the included tumors was assessed for MSI-H/MMR-D and 2 were assessed for MSI-L/MMR-D status. Studies on SBA, endometrial cancer, and CRC have reported differences between MSI testing and IHC [21,22,25]. The other 11 cases showed microsatellite stability (MSS).…”
Section: Discussionmentioning
confidence: 99%
“…The complete expression of all four MMR proteins was considered a case of pMMR. The loss of at least one MMR protein was considered a case of dMMR [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In endometrial cancer, the incidence of mutations in mismatch repair genes (MMR) is estimated at 17-30% [3][4][5]. The proteins of the MMR system are arranged in dimers, MLH1 together with PMS2 and MSH2 together with MSH6.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the microsatellite instability (MSI) phenotype by these techniques is validated by standardized guidelines that confirm the direct association between MMR genetic study and protein assessment [7][8][9]. The distinction between patients with MSI phenotype and those with stable phenotype (MSS) allows the identification of patients who are candidates for MMR germline testing and the differentiation of Lynch syndrome cases from sporadic cases, as they present different anatomoclinical, prognostic and therapeutic factors [4].…”
Section: Introductionmentioning
confidence: 99%